2005
DOI: 10.1080/14767050500127716
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental effects of allopurinol on suppression of oxygen free radical production in chronically instrumented fetal lamb brains during intermittent umbilical cord occlusion

Abstract: These results demonstrated a good transfer of allopurinol from mother to fetus and suggested the possibility of intrauterine treatment to inhibit fetal brain damage resulting from increased oxygen free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
(41 reference statements)
0
35
0
Order By: Relevance
“…However, animal studies have proven that allopurinol and oxypurinol pass through the blood/brain barrier and cause therapeutic concentrations in brain perfusate and cerebrospinal fluid. 9 10 Also, further experimental research in several species shows brain protection when allopurinol is given upon reperfusion and reoxygenation. 4 In addition, we feel that the relatively late start of the treatment, three to four hours after reperfusion, may have played an important role here.…”
Section: Discussionmentioning
confidence: 99%
“…However, animal studies have proven that allopurinol and oxypurinol pass through the blood/brain barrier and cause therapeutic concentrations in brain perfusate and cerebrospinal fluid. 9 10 Also, further experimental research in several species shows brain protection when allopurinol is given upon reperfusion and reoxygenation. 4 In addition, we feel that the relatively late start of the treatment, three to four hours after reperfusion, may have played an important role here.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 other studies in the literature have reported on antenatally administered allopurinol, but none of them have described any effects on the histology of the brain. 18,19,22,23,43 In the present study, therapeutic ranges of allopurinol and its metabolite oxypurinol have shown to be attainable after antenatal maternal treatment with allopurinol, while no adverse side effects were observed. These findings are in line with previous studies in both animals and humans.…”
Section: Discussionmentioning
confidence: 82%
“…18,22,23,43 Masaoka et al were the first to investigate antenatally administered allopurinol during intermittent umbilical cord occlusion in fetal sheep and described a significantly reduced production of superoxide in the allopurinol-treated animals. 22 This indicates a direct effect of allopurinol in preventing the production of free radicals, in scavenging free radicals once formed, or both. These results were confirmed in the ovine fetuses used in the present study, in which we found reduced indices of oxidative stress in the cardiovascular system after maternal treatment with allopurinol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allopurinol is metabolised into the active metabolite oxypurinol, which blocks uric acid production. Its plasma concentrations are therefore used in the monitoring of gout patients 21 22…”
Section: Introductionmentioning
confidence: 99%